Effects of sediment on fish communities in East Cape streams, North Island, New Zealand - Richardson, J.; Jowett, I. G. (New Zealand journal of marine and freshwater research, 2002)
We examined the effects of sediment on fish communities at 38 sites in the East Cape region of New Zealand. Many streams in this region are subject to high sediment loads, a natural situation that has been exacerbated by the conversion of native forest to pasture. The fish community consisted of diadromous native species common throughout New Zealand that require access to and from the sea. We found that site altitude and distance inland were important factors in determining the abundance and composition of the fish community. We used four measures as indices of sediment load: suspended sediment concentration, median substrate size, substrate stability, and the ratio of the wetted width to the width of the active (non-vegetated) stream channel. Although all indices were correlated, the ratio of wetted width to width of active channel was most closely related to fish abundance and diversity. Fish abundance and diversity reduced as sediment load increased among streams, with up to nine fish species in streams with low sediment loads and only two species in streams with high sediment loads. In-stream habitat also varied with sediment load; as load increased, depth and substrate size decreased and velocity increased. These results suggest that activities that increase sediment loads in rivers will have a negative impact on native fish communities in New Zealand.